1990
DOI: 10.1002/j.1552-4604.1990.tb01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Efficacy of Guanfacine and Prazosin in Patients with Mild to Moderate Essential Hypertension

Abstract: Guanfacine, an alpha 2 adrenoceptor agonist, was compared with prazosin hydrochloride for the treatment of patients with mild to moderate essential hypertension in an 8-week, double-blind, randomized, parallel evaluation to determine efficacy and safety. The study consisted of a 2-week screening/weaning period (phase I), a 3-week treatment period with chlorthalidone 25 mg every morning (phase II), and an 8-week double-blind treatment period with diuretic plus prazosin or guanfacine (phase III). Those who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Consistent with guanfacine's known effects as an antihypertensive and similar to previous studies of guanfacine extended release, guanfacine extended release was associated with a dose‐dependent decrease in BP and HR. In this study, it was shown that the physiologic HR response to standing (i.e., an increase) is preserved during treatment with guanfacine extended release.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with guanfacine's known effects as an antihypertensive and similar to previous studies of guanfacine extended release, guanfacine extended release was associated with a dose‐dependent decrease in BP and HR. In this study, it was shown that the physiologic HR response to standing (i.e., an increase) is preserved during treatment with guanfacine extended release.…”
Section: Discussionsupporting
confidence: 86%
“…Guanfacine decreases blood pressure (BP) and heart rate (HR) through stimulation of α 2 ‐adrenoceptors in the brain stem . Several studies of adult subjects with mild to moderate hypertension have found that treatment with guanfacine (1–3 mg/day) significantly reduced both seated and standing systolic BP (SBP) and diastolic BP (DBP) as well as HR . Rebound hypertension and increases in HR have been noted upon rapid withdrawal of clonidine, another α 2 ‐adrenergic agonist, in hypertensive patients .…”
mentioning
confidence: 99%
See 1 more Smart Citation